How do you simplify #(2xyz)/(x^2z^2)div (6y^3)/(3xz)#?

1 Answer
Mar 2, 2017

Answer:

#\frac{1}{y^2}#

Explanation:

When we divide one fraction with another one, we can rewrite it as multiplication of first fraction by the second one, it means:
#a/b -: c/d = a/b \times d/c = (ad)/(bc)#

so let's do the trick and see what'll happen
# \frac{2xyz}{x^2z^2} -: \frac{6y^3}{3xz} = \frac{2xyz}{x^2z^2} \times \frac{3xz}{6y^3}#

and we simply multiply the numerator by the numerator and the denominator by the denominator.
# \frac{2xyz}{x^2z^2} \times \frac{3xz}{6y^3} = \frac{6x^2yz^2}{6x^2y^3z^2}#
and by simplifying this fraction we get:

#\frac{6x^2yz^2}{6x^2y^3z^2} = \frac{1}{y^2}#